Hepatitis B carriage and Brucella seroprevalence in urban and rural areas of Bolu province of Turkey: A prospective epidemiologic study - Oğuz KARABAY; Erdinç SERİN; Ali TAMER; Feray GÖKDOĞAN; Hacer ALPTEKER; Arzu ÖZCAN; Hüseyin GÜNDÜZ (Turkish Journal of Gastroenterology, 2019)
-